"Be Their Advocate": Families' Experience with a Relative in LTC during the COVID-19 Pandemic. Issue 4 (13th December 2021) - Dupuis-Blanchard, Suzanne; Maillet, Danica; Thériault, Danielle; LeBlanc, Félix; Bigonnesse, Catherine
Abstract: Shortly after the COVID-19 pandemic was declared, strict visitor restrictions were issued for long-term care facilities (LTCFs). A year later, restrictions are still in place and they continue to impact family members who have limited or no in-person contact with their relative in LTCFs. The goal of this qualitative longitudinal focused ethnography was to understand the experience of family members who have a relative in a LTCF where visiting has been restricted during the pandemic. Seventeen family members participated in two interviews that were 6 months apart. Data analysis highlighted five key drivers, defined as the workforce, communication deficits, characteristics of care, public health directives, and autonomy of relative which in turn resulted in three main themes: psychological distress, surveillance, and visiting challenges. This study provides a glimpse into the difficult experiences of families with a relative residing in a LTCF in the province of New Brunswick.